A model for the early diagenesis of humid climate, fluvial strata influenced by adjacent salt deposits: Grande Anse Formation, Cumberland Basin, Canada. Issue 7 (11th June 2022) - Bahr, Fadel; Keighley, Dave
Abstract: Diagenetic models help explain reservoir quality of siliciclastic strata, which are globally important exploration targets for groundwater, petroleum and carbon sequestration. Siliciclastics occur in salt provinces worldwide but remain poorly studied despite documented deviation from basic eodiagenetic models. A new variation is explained based on evidence from Cumberland Basin strata (Grande Anse Formation, Pennsylvanian, Canada). These strata were deposited in a fluvial setting under semi‐humid to humid climates and represent an unconformable cover sequence over a salt wall. Optical microscopy and scanning electron microscopy, both employing cathodoluminescence, reveal that widespread early diagenetic phases are mostly deleterious to reservoir quality. These pre‐compactional eodiagenetic phases are: (i) variable dissolution/alteration of feldspars, micas and carbonate/evaporite clasts; clay and grain staining iron oxides; and pore‐filling kaolinite; (ii) microcrystalline calcite; quartz overgrowths, prismatic quartz, quartzine chalcedony and blocky quartz, the latter two pseudomorphous after gypsum; and barite; (iii) framboidal pyrite and locally extensive Mg, Fe and Mn‐bearing blocky calcite. The first phase is attributed to a seasonally wetted vadose zone under relatively low pH and positive Eh conditions characteristic of humid climates. In contrast, the second phase is usually associated with evaporitic conditions and arid climates, where authigenesis occurs in the capillary fringe to just below the water table, and where porewaters are much more saline. The third phase is related to authigenesis from shallow burial, anoxic, phreatic porewaters. How is the aforementioned humid/arid dichotomy deciphered? Important may be the distinction between vadose and circum‐water‐table phases. Beneath vadose deposits of the humid climate, the proximity of evaporite rock in the salt wall allows for its localized dissolution, providing abundant Ca, CO3 and SO4 ions to produce anomalously saline, shallow groundwater. Barite and transient gypsum precipitated, the latter subsequently replaced by chalcedony and pseudomorphous silica during sporadic events where flushing of meteoric water temporarily lowered pH.